KENDALA DAN KENDALI PENGUASAAN BAHASA ASING DI MADRASAH - Sribagus Sribagus (SOCIETY, 2018)
It is assumed that Arabic is the language mainly used at Madrasah. It turns to be the other way around – hardly any teacher uses Arabic communicatively as the classroom language instruction, and hardly any student actively speaks in it fluently outside the classroom. Teachers teach traditionally, applying “Learning System” which brings about memorization of language codes/rules and vocabulary enrichment. Using language communicatively is beyond the intended target as stated in the curriculum. The alternative solutions are the changing of teaching and learning method from Learning to Acquisition, and providing the language input from the early start of class activity.